Novel induction therapy transoral surgery treatment paradigm with risk-adapted adjuvant therapy for squamous cell carcinoma of the head and neck – Mature clinical and functional outcomes. (November 2020) - Hackman, Trevor G.; Patel, Samip N.; Deal, Allison M.; Neil Hayes, D.; Chera, Bhishamjit S.; Paul, Jennifer; Knowles, Mary; Usenko, Dmitriy; Grilley-Olson, Juneko E.; Weissler, Mark C.; Weiss, Jared
Highlights: Induction therapy followed by transoral surgery is feasible in a Phase II trial. A risk-adaptive approach to treatment of head and neck cancer is effective. Surgical and functional outcomes after induction therapy are excellent in head and neck cancer. Induction therapy followed by transoral surgery reduces adjuvant therapy need. Longterm survival outcomes after induction therapy and surgery are excellent. Abstract: Objective: Induction chemotherapy in head and neck squamous cell carcinoma (HNSCCA) has principally been studied prior to radiation therapy. We evaluated pre-operative induction therapy followed by surgery followed by risk-adapted adjuvant therapy. This report details the mature 5-year survival statistics, clinical and functional outcomes. Methods: An IRB-approved single institution prospective phase II clinical trial from October 2012 to November 2016 was conducted for patients with transorally-resectable American Joint Committee on Cancer 7th ed. stage III/IV HNSCCA. Patients were treated once weekly for six weeks with a multi-drug induction regimen of carboplatin, paclitaxel and daily lapatinib followed by transoral surgery and neck dissection. Patients were then stratified based on pathologic response to either observation or adjuvant therapy. Survival statistics and functional patient outcomes were analyzed. Specifically, peri-operative outcomes were analyzed and compared to a matched surgical cohort. Results: 38/40 enrolled patients completed trial therapy. Median hospital stay was 3 days with 9/38 patients receiving a PEG (median 46 days). Median NPO status was 1 day, with a median return to a regular diet in 16 days. Mean patient weight was well preserved from pretreatment to 1 year after surgery (85.1 kg (95% CI 79.6–90.7) vs 83.1 kg (95% CI 77.7–88.6 kg) respectively). Of the 38 patients who completed trial therapy; DSS, PFS and OS were 100%, 97% and 97% respectively with median follow up of 4.9 years (3.33–7.25). Conclusion: Transoral surgery was feasible following this novel induction regimen with excellent peri-operative, functional and longterm survival outcomes.